2001
DOI: 10.1007/s007010170079
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Cerebrospinal Fluid Distribution and its Postoperative Changes in Normal Pressure Hydrocephalus

Abstract: These results suggest that patients with NPH have a unique intracranial CSF distribution, with an enlarged VV and a slightly increased ICV, resulting in a high VV/ICV ratio. Shunting led to dramatic improvement in our patients. It is likely that CSF measurement can provide valuable information in the management of patients with NPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The median postoperative decrease in VV (25 mL) in shunted patients with iNPH was similar to that found in previous studies. [14][15][16] The proportional postoperative decrease in ventricle size was .3 times greater when measuring VV (18%) compared with the EI (5%). Furthermore, the decrease in VV in the interval of 20-40 mL and the increase in the iNPH scale score were more strongly correlated than the decrease in the EI and the increase in the iNPH scale score; the mean increase in the iNPH scale score was 16.4 per 1-SD decrease in VV compared with 7.6 per 1-SD decrease in the EI.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The median postoperative decrease in VV (25 mL) in shunted patients with iNPH was similar to that found in previous studies. [14][15][16] The proportional postoperative decrease in ventricle size was .3 times greater when measuring VV (18%) compared with the EI (5%). Furthermore, the decrease in VV in the interval of 20-40 mL and the increase in the iNPH scale score were more strongly correlated than the decrease in the EI and the increase in the iNPH scale score; the mean increase in the iNPH scale score was 16.4 per 1-SD decrease in VV compared with 7.6 per 1-SD decrease in the EI.…”
Section: Discussionmentioning
confidence: 95%
“…11 Furthermore, decreases in EI have been shown to be poorly correlated with clinical improvement after shunt surgery, 12,13 whereas recent studies evaluating ventricular size by means of volumetric measurements have shown mean postoperative decreases of VV of 24%-28% in patients with improved iNPH, suggesting that such measurements may constitute more clinically relevant markers. [14][15][16][17] Currently, there are no large-scale studies comparing postoperative changes in VV and the EI in patients with iNPH. Here, we evaluated postoperative changes in VV and the EI and investigated their relation to clinical outcome.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6][7] A downside in the investigation of the postshunt reduction of ventricular size is that the amount of CSF that has actually flowed through the shunt is unknown. The increased outflow resistance and dilated ventricles, 1 without a concomitant increase in intracranial pressure, has yet to have an explanation fitting both clinical observations and the laws of physics.…”
mentioning
confidence: 99%